2016
DOI: 10.1093/ntr/ntw026
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Cue Attentional Bias in Cocaine-Smoking and Non-Cocaine-Using Cigarette Smokers

Abstract: Introduction: Cigarette smoking in cocaine users is nearly four times higher than the national prevalence and cocaine use increases cigarette smoking. The mechanisms underlying cigarette smoking in cocaine-using individuals need to be identified to promote cigarette and cocaine abstinence. Previous studies have examined the salience of cigarette and cocaine cues separately. The present aim was to determine whether cigarette attentional bias (AB) is higher in cigarettes smokers who smoke cocaine relative to ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…The choice bias observed reproduced those effects observed in Experiments 1 and 2, indicating that the outcome was not bound by the specific task parameters used in those earlier experiments. The significance and magnitude of the fixation time attentional bias observed also reproduced similar outcomes in recent studies evaluating cocaine cue attentional bias using a visual probe method (Marks et al 2014a, 2014b, 2015, 2016). Results with another measure (i.e., percentage final fixation scores) were also consistent with an attentional bias towards cocaine-related cues.…”
Section: Discussion: Experimentssupporting
confidence: 84%
See 2 more Smart Citations
“…The choice bias observed reproduced those effects observed in Experiments 1 and 2, indicating that the outcome was not bound by the specific task parameters used in those earlier experiments. The significance and magnitude of the fixation time attentional bias observed also reproduced similar outcomes in recent studies evaluating cocaine cue attentional bias using a visual probe method (Marks et al 2014a, 2014b, 2015, 2016). Results with another measure (i.e., percentage final fixation scores) were also consistent with an attentional bias towards cocaine-related cues.…”
Section: Discussion: Experimentssupporting
confidence: 84%
“…Supporting these theories is research showing greater visual attention to laboratory conditioned cues (e.g., Hogarth et al 2003; Mayo and de Wit 2015). Recent research has demonstrated attentional bias in cocaine users by demonstrating a robust, reliable, and selective bias for cocaine cues (Leeman et al 2014; Marks et al 2014a, 2014b, 2015, 2016).…”
Section: Discussion: Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the attentional bias (AB; Williams et al, 1988) seem to be particularly relevant, as shown by several studies in different areas such as anxiety disorders (Pool et al, 2016), food consumption (Deluchi et al, 2017), alcohol abusers (Manchery et al, 2017) and cocaine users (Marks et al, 2016). A plethora of studies reported this effect to be present also within smokers (Bradley et al, 2003; Drobes et al, 2006; Munafò et al, 2003; Waters et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…The positive correlations observed among all three networks and cocaine use via two-way interactions with tobacco can be attributed to the concurrent use of both cocaine and tobacco (Marks et al, 2016), with the latter acting as a gateway to cocaine use (Kandel and Kandel, 2015). The positive correlation between VS connectivity and both cocaine as well as opiates could be indicative of “speedball” use.…”
Section: Discussionmentioning
confidence: 99%